Measuring and Decomposing Productivity of Co-operatives in Aceh, Indonesia - M. Shabri Abd. Majid; Faisal Faisal; Heru Fahlevi; Azhari Azhari (ETIKONOMI, 2022)
This study empirically assesses the co-operatives' productivity across 23 districts/cities in Aceh province, Indonesia, over 2014-2018 using the Malmquist Total Factor of Productivity Index (MTFPI) based on Data Envelopment Analysis (DEA). Unlike previous studies that focused only on selected sectors and industries, this study examines the co-operative productivity of all industries and sectors within one province. Overall, this study recorded a low productivity level of co-operatives. Only co-operatives in Subulussalam City consistently experienced a fully productive using both Constant Return to Scale (CRS) and Variable Return to Scale (VRS) estimations. Meanwhile, based on the VRS estimation, the study found that the co-operatives in Aceh Besar and Aceh Utara's districts had experienced total productivity. Overall, the co-operatives' productivity level has slightly declined, contributed mainly by a decline in technical efficiency. However, the co-operatives' efficiency level has increased, mainly due to their scale efficiency improvement. The findings suggested the importance of implementing sound co-operative governance principles and enhancing technical efficiency by adopting e-marketing and the internet of things in their business activities.How to Cite:Majid, M.S.A., Faisal, F., Fahlevi, H., & Azhari, A. (2022). Measuring and Decomposing Productivity of Co-operatives in Aceh, Indonesia. Etikonomi, 21(1), 55-66. https://doi.org/10.15408/etk.v21i1.21299.